Improvement of Diagnosis by Transvaginal Ultrasound and Prognosis of Endometrial Cancer using miR-222-3p: A Prospective Cohort Study - Shengrong Feng; Yinping Huang; Juan Liao; Chunlv Huang; Ruojun Zhao; Min Zeng (Clinical and Experimental Obstetrics & Gynecology)
Background: Noninvasive biomarkers need identification to enhance the diagnostic accuracy of endometrial cancer (EC) detection. The diagnostic and prognostic significance of serum miR-222-3p in EC was investigated in this study to provide a reference for clinical diagnosis and treatment. Methods: This prospective cohort study comprised 128 patients with EC and 65 patients with benign endometrial lesions (benign endometrial hyperplasia or polyps) admitted to Qionglai Medical Centre Hospital from January 2016 to December 2018. EC diagnosis was confirmed through endometrial biopsy and postoperative pathology. Serum miR-222-3p levels were quantified using the real-time reverse transcriptase-polymerase chain reaction (RT-qPCR). Pearson’s method was utilized to assess correlations between miR-222-3p and the resistance index (RI), pulsation index (PI), and mean blood flow velocity (MBFV). Diagnostic and prognostic assessments of miR-222-3p were conducted using receiver operating characteristic (ROC) curve analysis, Cox regression analysis, and Kaplan‒Meier curve analysis. Results: Serum miR-222-3p levels were higher in EC patients compared to controls and were correlated with RI, PI, and MBFV (p < 0.001). Serum miR-222-3p enhanced the sensitivity (69.53% vs. 96.88%) and specificity (92.31% vs. 96.92%) of transvaginal ultrasound for EC diagnosis. Furthermore, serum miR-222-3p showed significant associations with lymph node metastasis (p = 0.002), degree of differentiation (p = 0.023), and the International Federation of Gynecology and Obstetrics (FIGO) stage (p = 0.001) in EC patients. It also predicted poor prognosis and served as an independent prognostic predictor (p = 0.036). Conclusions: The combination of miR-222-3p with transvaginal ultrasound enhanced the diagnostic efficiency of EC. Additionally, miR-222-3p holds promise as a biomarker for predicting the prognosis of EC patients.